Treatment of femoral neck fractures: sliding hip screw or cannulated screws? A meta-analysis - Xia, Yutong (J Orthop Surg Res, 2021)
PURPOSE: Femoral neck fractures are still unsolved problems nowadays; sliding hip screw (SHS) and cannulated compression screw (CCS) are the most commonly used devices. We evaluated the clinical outcomes and complications in the treatment of femoral neck fractures between SHS and CCS in this meta-analysis to find which is better. METHODS: We searched PubMed, Embase, Cochrane library up to 24 August 2020 and retrieved any studies comparing sliding hip screw and cannulated compression screw in treatment of femoral neck fractures; the main outcomes and complications were extracted from the studies which were included. RESULTS: Nine studies involving 1662 patients (828 patients in the SHS group and 834 patients in the CCS group) were included in this study. SHS had higher rate of avascular necrosis (RR = 1.30, 95% CI 1.08–1.56, p = 0.005), and CCS had higher rate of implant removal (RR = 0.63, 95% CI 0.43–0.93, p = 0.02). No significant statistical difference in non-union, implant failure, infection, replacement, mortality, orthopedic complications, non-orthopedic complications, and total revision between SHS and CCS group. CONCLUSION: Both devices have their pros and cons; SHS had a higher rate of avascular necrosis, and CCS had a higher rate of implant removal rate. No significant statistical difference in non-union, implant failure, infection, replacement, mortality, orthopedic complications, non-orthopedic complications, and total revision between SHS and CCS group.